Most effective mean for lactate clearance in Olympic wrestling - Mazuera-Quiceno, C. A.; Dávila-Grisalez, A. A.; Calderón-González, J. C.; Palacios-Ruales, Y. M.; Tobar-Gutiérrez, A. (Retos: nuevas tendencias en educación física, deporte y recreación, 2022)
This research project determined the most effective training mean for lactate clearance using the subaerobic functional area in Olympic wrestling athletes of the freestyle modality. Eight Olympic wrestlers participated (age: 20.1±2.74 years), using a four-phase crossover study design, in which the athlete performed active recovery alternating each of the training means (Elliptical machine, treadmill, crank ergometer and stationary bicycle); lactate samples were taken 5 minutes after each bout and 15 minutes after finishing the active recovery. The elliptical machine presented the highest average efficiency, with 56.6%, followed by the treadmill with a 54.1% efficiency average; the repeated measures ANOVA F test evidenced differences among the means (p = .001). Likewise, differences were found when performing the post hoc comparisons of minimal significant difference, between the elliptical machine with respect to the crank ergometer (p = .001) and the stationary bicycle (p = .007), but they were not registered between the elliptical machine and the treadmill (p = .737). Of the means analyzed in this study, the highest efficiency in the process of blood lactate clearance during active recovery was evidenced by the elliptical machine and treadmill.